Media Sosial, Fasilitas Kerja, dan Kinerja Pegawai: Studi pada Dinas Pendidikan Morowali Utara - Abdullah, Megawati Putri; Niluh Putu Evvy Rossanty; Andi Indriani Ibrahim; Moh. Zeylo Auriza (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to determine the effect of social media and work facilities on employee performance at the North Morowali Regency Education and Culture Office. This is a quantitative study that identifies independent variables, namely social media and work facilities, with dependent variables, namely performance, with a sample size of 80 people. The sampling technique used was saturated sampling, where all members of the population were included in the sample if the population size was relatively small, less than 30 people. A saturated sample is referred to as a census. The results of this study show that: 1) Based on the results of hypothesis testing, it is known that the variables of Social Media (X1) and Work Facilities (X2) have a significant effect on employee performance at the North Morowali Regency Education and Culture Office. 2) Social Media has a positive and significant effect on employee performance at the North Morowali Regency Education and Culture Office. 3) Work Facilities have a positive and significant effect on employee performance at the North Morowali Regency Education and Culture Office.